1992
DOI: 10.1016/0926-860x(92)85072-j
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of methanol dehydrogenation on a sodium carbonate catalyst

Abstract: The aim of this study is to identify the reaction mechanism of methanol dehydrogenation on sodium carbonate catalyst. Quantitative analyses of the products of methanol dehydrogenation on sodium carbonate catalyst at 963 K indicate that methane is formed in parallel with formaldehyde, while carbon monoxide is mainly produced from further decomposition of formaldehyde. In a specially designed fixedbed reactor, more than half of the methanol conversion takes place in the post-catalytic space, where the selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…They vary in the range of 0.80-0.95 at conversions less than 0.6 and decrease steeply to zero at complete conversion due to consecutive decomposition of formaldehyde. Only carbon monoxide and methane are significant by-products, which is the same as for the Na2C03 catalyst [5]. These observations suggest that the main products are formed through reactions on Na2C03 in the mixtures, and that the additives promote only the rate-limiting step of the reaction on Na2C03.…”
Section: Promoting Effects Of Active Carbons and Metalssupporting
confidence: 54%
“…They vary in the range of 0.80-0.95 at conversions less than 0.6 and decrease steeply to zero at complete conversion due to consecutive decomposition of formaldehyde. Only carbon monoxide and methane are significant by-products, which is the same as for the Na2C03 catalyst [5]. These observations suggest that the main products are formed through reactions on Na2C03 in the mixtures, and that the additives promote only the rate-limiting step of the reaction on Na2C03.…”
Section: Promoting Effects Of Active Carbons and Metalssupporting
confidence: 54%
“…In a kinetic study, a catalyst-initiated homogeneous reaction was found important with sodium carbonate as catalyst [52]. It accounts for over half of the total conversion.…”
Section: Sodium Carbonate Catalystsmentioning
confidence: 99%
“…Brackman (1959) reported that by passing oxygen through a stirred mixture of liquid methanol and cupric nitrate tri-hydrate complex at 298.15 K, an 80% yield of formaldehyde based on the amount of oxygen consumed can be achieved. Dehydrogenation of methanol is another subject that has been discussed by some Brought to you by | University of Pittsburgh Authenticated Download Date | 1/5/15 7:37 AM researchers (Sabatier and Mailhe 1910, Newton and Dodge 1933, Sexton 1981, Su et al 1992, Zaza et al 1994); Sabatier and Mailhe (1910) studied this process and declared that this reaction is a reversible one. Later, Newton and Dodge (1933) derived the following equilibrium relation for this reversible reaction:…”
Section: Other Formaldehyde Production Methods From Methanolmentioning
confidence: 97%